2012
DOI: 10.1002/ejlt.201100393
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactobacillus plantarum P‐8 on lipid metabolism in hyperlipidemic rat model

Abstract: Probiotics have been reported to play an important role in the prevention of metabolic disorders. We recently identified a novel probiotic strain Lactobacillus plantarum (L. plantarum) P-8. The objective of this study was to determine the effects of L. plantarum P-8 on lipid metabolism of rats fed with high fat diet. All experimental rats were divided into three groups: control group, model group, and L. plantarum P-8 group. Changes in serum lipid levels, hepatic lipid deposition, serum oxidative stress-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 33 publications
(34 reference statements)
5
37
0
1
Order By: Relevance
“…1). This confirms the results of Bao et al 24 who showed that L. plantarum P-8 was also effective in preventing liver injury based on results from ALT and AST analysis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…1). This confirms the results of Bao et al 24 who showed that L. plantarum P-8 was also effective in preventing liver injury based on results from ALT and AST analysis.…”
Section: Discussionsupporting
confidence: 91%
“…4,22 Meanwhile, our previous studies have shown that some gut bacteria (namely Bacteroides, Clostridium, Eubacterium, Escherichia, and Lactobacillus) were increased in rats given LIP-1 cells, which were known to deconjugate bile salts in the gut and enhance CHO excretion. 23 Bao et al 24 showed similar results for the influence of L. plantarum P-8 on lipometabolism in humans. Dvir et al 25 also found a CHOlowering potential for red microalga, mainly caused by enhanced excretion.…”
Section: Discussionmentioning
confidence: 68%
“…1). This confirms the results of Bao et al [22] who showed that L. plantarum P-8 was also effective on the prevention of liver injury based on results from ALT and AST analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Meanwhile, our previous studies have shown that some gut bacteria (namely Bacteroides, Clostridium, Eubacterium, Escherichia and Lactobacillus) were increased in rats given LIP-1 cells, which were known to deconjugate bile salts in the gut and enhance cholesterol excretion [21]. Bao et al [22] showed similar results for the influence of L. plantarum P-8 on lipometabolism in humans. Dvir et al [23] also found a cholesterol-lowering potential for red microalga, mainly caused by enhanced excretion.…”
Section: Discussionmentioning
confidence: 80%
“…through the basic local alignment search tool ( ncbi ‐ blast ). Lactobacillus casei Zhang (LCZ), Lactobacillus plantarum P8 (LP) and S. thermophilus ND03 (ST) were provided by the Key Laboratory of Dairy Biotechnology and Engineering, Ministry of Education, China (Sun et al ., ; Bao et al ., ; Wang et al ., ).…”
Section: Methodsmentioning
confidence: 99%